2019
DOI: 10.1177/0036850419875667
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic analysis and simulation of a new type of differential micro-feed mechanism with friction

Abstract: This article presents a new micro-feed mechanism, whose main transmission component is the nut–rotary ball screw pair. The screw and nut are driven by two motors, and they rotate in the same direction, with their movements enabling micro-feeding. The main contribution of the micro-feed mechanism is to avoid the inevitable low-speed nonlinear creeping phenomenon caused by the inherent properties of traditional electromechanical servo system structure, thus realizing high precision micro-feed. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the case of crawler guide rail dual drive, there is no nonlinear friction force between the table and the “crawler type” guide rail because the relative speed of the two is zero. The equations of motion for the crawler guide rail dual drive system are 14 :…”
Section: Dynamic Model Of the Crawler Guide Rail Dual Drive Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of crawler guide rail dual drive, there is no nonlinear friction force between the table and the “crawler type” guide rail because the relative speed of the two is zero. The equations of motion for the crawler guide rail dual drive system are 14 :…”
Section: Dynamic Model Of the Crawler Guide Rail Dual Drive Systemmentioning
confidence: 99%
“…Servo motor has the advantages of high precision, fast response, etc., for AC servo system PMSM after appropriate simplification the command signal through the position, velocity, and current feedback gain obtain the output torque. The current equation is given by 13 14 …”
Section: Friction Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of the friction model depends on a variety of different physical characteristics and operational circumstances [15] because friction is complex and nonlinear [16]. To identify the parameters for the TDMS, the LuGre friction model [17] and feed-forward friction compensation [18] were used, but the LuGre model fails to effectively capture the nonlocal memory phenomenon [19]. In contrast to the experience-based friction model discussed above, the general Maxwell Sliding sliding [20] model was used from a microscopic perspective to explain the observed macroscopic friction behavior, describe the hysteresis above, the general Maxwell Sliding sliding [20] model was used from a microscopic perspective to explain the observed macroscopic friction behavior, describe the hysteresis curve using the Maxwell sliding model, and address the problems above.…”
Section: Introductionmentioning
confidence: 99%
“…Wei and Lai 19 derived the transmission efficiency formula by calculating the theoretical driving torque, axial load, and angular speeds of the working ball, and this formula was verified by the experimental data. Yu et al 20 analyzed the motion state of the working ball using the principle of differential geometry, and the transmission efficiency of the ball screws was calculated. The results showed that the transmission efficiency displays an increasing trend at a low speed.…”
Section: Introductionmentioning
confidence: 99%